ASSESSMENT OF CANINE NEONATE BY APGAR SCORING SYSTEM AND ITS VALUE AS AN INDEX OF SHORT TERM NEONATAL SURVIVAL - JAYAKUMAR, C; KRISHNASWAMY, A; SUDHA, G; HONNAPPA, T G (The Indian Journal of Animal Reproduction, 2023)
Early recognition of neonatal distress is crucial for optimal neonatal health, which envisages theassessment of the newborn for its viability status. The study aimed to evaluate the worth of Apgar score system in assessment of the clinical status of the newborn in dogs and its efficiency in timely neonatal care. The value of the Apgar score system in predicting the neonatal survivability was also assessed. The study confirmed thesignificance of Apgar scoring as a simple and reliable evaluation system in canine neonates that may help in identifying the distressed puppies and thereby reduce the incidence of neonatal mortality. The relevance of Apgar scoring system for short term survival prognosis in canine neonates was also established.
Keywords: Neonate; Canine; Apgar score; Survival